Perception of IIUM Staff towards the ethicality of Islamic banking products and services in the light of Maqasid al-shari‘ah - Sumairi, Nor Sazwana; Musa, Muhammad Adli; Ahmad, Nadzrah (International Islamic University Malaysia, 2017)
Ethics is a discipline that deals with “the science of conduct”, which is concerned with two opposing dimensions of moral action such as right or wrong, good or bad, and virtue or vice. In the context of Islamic finance, ethics has become a vital component in the financial services sectors in order to provide “value” for consumers. Unfortunately, the current practices of Islamic financial institutions have been criticised for their failure to promote such values. The products and services offered by Islamic financial institutions must meet the requirement of the shari’ah, where all transactions are void of any illegal and unethical elements. There are numerous Qur’anic injunctions and Prophetic traditions concerning ethical principles pertaining to Islamic finance, particularly those related to ethics of business transactions. Ethics should be uncompromisingly infused in financial transactions to curb corruption, injustice, and exploitation, and this is all consistent with objectives of the Shari’ah (maqasid al-Shari‘ah). This study employs a quantitative method by surveying consumer perception on the ethicality and “Islamicness” of Islamic finance products and services through a structured questionnaire comprising close-ended questions. It is thus important to educate consumers about ethical finance, enhance ethicality of Islamic finance through specific standards, and encourage Islamic financial institutions to demonstrate their commitment and efforts in providing added values to consumers.